Liquidity Fluctuations in Over‐the‐Counter Markets - MAURIN, VINCENT (Journal of Finance, 2022)
ABSTRACTThis paper proposes a theory of excess price fluctuations in over‐the‐counter secondary markets. When heterogeneous assets trade under asymmetric information, a quality effect emerges: high liquidity lowers the quality of the pool of sellers and decreases future liquidity. Cyclical equilibria can arise even without fundamental shocks. In a cycle, investors speculate by bidding up the price of low‐quality assets, anticipating a high resale price at the peak. When this resale effect is strong, cycles disappear and multiple steady states coexist with different levels of liquidity. The model rationalizes empirical patterns for corporate bonds and housing in particular.